The defluorination of perfluorooctanoic acid by different vacuum ultraviolet systems in the solution. (15th September 2020) - Li, Yuanhao; Lin, Qiufeng; Li, Cong; Weiguo, Zijian; Xu, Luo; Zhang, Kejia
Abstract: Perfluorooctanoic acid (PFOA) is one kind of persistent organic pollutants that is often detected in water. In recent years, the effective degradation technologies of PFOA have attracted widespread attentions. Thus, in this study, the defluorination efficiency of PFOA in different systems (i.e., ultraviolet (UV), vacuum ultraviolet (VUV), vacuum ultraviolet/persulfate (VUV/PS) and vacuum ultraviolet/residual chlorine (VUV/RC)) was evaluated. Moreover, the different impact factors (i.e., the initial concentrations of persulfate and PFOA, temperature, anions, and initial pH values) on PFOA degradation by VUV/PS system were investigated. The results showed that VUV system was more effective than UV system for PFOA defluorination. VUV system combined with persulfate would further enhance the defluorination efficiency while residual chlorine would decrease it. In VUV/PS system, the defluorination efficiency of PFOA was the best as the molar ratio of PFOA and persulfate at 1:60. Moreover, higher temperature, lower initial PFOA concentration, and acid condition were favorable for the defluorination of PFOA. Under the different influence factors, the defluorination efficiency of PFOA fitted well to the first‐order reaction kinetic model. When the temperature was range from 20°C to 40°C, the value of activation energy was 8.73 kJ/mol. Besides, the inhibition effect of three kinds of anions on PFOA defluorination followed the order: NO 3 ‐ > Cl − > CO 3 2 ‐ . Practitioner points: The defluorination efficiency of perfluorooctanoic acid (PFOA) in water by different VUV systems was compared. VUV system is more effective than UV system for PFOA defluorination. Persulfate will enhance the defluorination efficiency by VUV system. Hypochlorite will decrease the defluorination efficiency by VUV system. Abstract : The defluorination of perfluorooctanoic acid by different VUV systems in the solution.